Organizacija i tehnologija javnog masovnog prevoza putnika u funkciji valorizacije objekata XIV ZOI Sarajevo 1984 - JAŠAREVIĆ, Faruk; ANIN KAFEDŽIĆ, Srećko (Promet - Traffic&Transportation, 2026)
ORGANIZATION AND TECHNOLOGY OF MASS PUBLIC PASSENGER TRANSIT IN THE SERVICE OF EVALUATION OF FACILITIES OF 1984 SARAJEVO XIV. WINTER OLYMPICS The authors commit to review the activities on organization of tourist transportation within the scope op preparations and during the XIV. Sarajevo Winter Olympic Games while the transport volumes were at the time absorbed by road traffic routes on the city/winter sports complex route. They reiterate the requirement for a maximum assessment of tourist and sports - recreation facilities in the mountainous area located in the immediate vicinity of Sarajevo after the Games in order to complete a more comprehensive evaluation of the facilities built.